PMP Exam Cram 2, Second Edition - Solomon, Michael 1963- (Pearson IT Certification, 2005)
The PMP Exam Cram 2, Second Edition provides PMP exam candidates a condensed and focused study vehicle. Organized for optimal learning of criccal project management steps, it covers all objective areas presented by PMI. Candidates using the PMP Exam Cram 2, Second Edition will be able to easily decipher and effectively use PMI's PMBOK. You'll also find notes, tips and cautions to extend on PMP content, and it will explain the differences between traditional methods of project management and what PMI considers to be good project management techniques. Exam Alerts will help alert you to content that will most likely appear on the PMP exam, and practice questions are found both in the book and on the accompanying CD-ROM. You'll even be prepared for last-minute studying with the Cram Sheet tearcard. Give yourself the best chance possible for a great test score with the PMP Exam Cram 2, Second Edition.
Keywords: Project management -- Study guides -- Examinations; Project management; Gestion de projet; Gestion de projet; Examens; Guides de l'étudiant; examination study guides; Study guides; Guides de l'étudiant